If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(f+3)+-3=21
We move all terms to the left:
2(f+3)+-3-(21)=0
determiningTheFunctionDomain 2(f+3)-3-21+=0
We add all the numbers together, and all the variables
2(f+3)=0
We multiply parentheses
2f+6=0
We move all terms containing f to the left, all other terms to the right
2f=-6
f=-6/2
f=-3
| 5x-2(4x+1)=7(2x-3)-15 | | 2(b+2)=20 | | 4x-8=76,x | | 12(x-3)+6=-3(x+5) | | 77=15x | | 7x+2(5x-16=16 | | 0.2x+3.5=0.7 | | 130-(3x-6)=8x+4 | | 7,500=36x+3,000 | | 16=-2w-9 | | 10u+5=5u+10 | | 14x7=9x-42 | | 5/6m=150.60 | | 23.65=8.95x+17.90 | | 3/4w=1464 | | 2g+2g-+3=43 | | 2w+w=7 | | 2h=-6 | | -x+3(-5+5x)=13 | | p/0.75=36.00 | | -3z+2z+5z=12 | | 10(x-2)+13=20 | | 5x+-6=-13 | | 9g-16g-3=-17 | | 3x+8-2(1-x)=x | | 4(6x+10)-8=66 | | 23.65=17.90x+8.95 | | 5a+56=55 | | 3(3+2y)=21 | | x(x+4)(5-2x)=0 | | 10=6+x/18 | | 8(1+7a=-272 |